Observations of pumping and vortex dynamics due to a cylinder oscillating normal to a plane wall. (10th December 2022) - Tom, J.G.; Draper, S.; Milne, I.A.; Zhou, T.; Zhao, M.
Abstract: Abstract : Understanding the fluid dynamics associated with a circular cylinder oscillating normal to a plane wall is important for safe design of offshore infrastructure, such as power cables and pipeline risers. This paper investigates the fluid dynamics of an oscillating cylinder with no imposed incident current experimentally using flow visualisation and force measurements where the ratio of the cylinder Reynolds number ( $Re$ ) to Keulegan–Carpenter number ( $KC$ ) is $β =500$ and $KC$ varies between 2 and 12. The minimum distance between the cylinder and wall was between 12.5 % and $50\, %$ of the diameter. Across this parameter space three primary vortex flow regimes were observed: (i) for $KC≤ 5$, the flow field is approximately symmetric about the cylinder centreline and the velocity field between the cylinder and the wall resembled a pumping flow in phase with cylinder motion, which is well predicted by potential theory for most of the cycle; (ii) for $5< KC<8$, the flow field is increasingly asymmetric but with frequent switching of the side associated with vortex shedding; and (iii) for $KC≥ 8$, the flow field is consistently asymmetric due to vortex shedding. The in-line force increases when the cylinder is near the wall due to dynamic pressures associated with pumping. This increase can be estimated using potential theory superimposed onto the force time history for an isolated cylinder at the same $KC$ and $Re$ . This study complements recent numerical modelling focused on low Reynolds number conditions and provides important insights into the fluid mechanics associated with trenching beneath cable and pipeline risers.